Extra virgin olive oil menurunkan kadar mda (Malondialdehyde) pada tikus (Rattus norvegicus) jantan galur wistar yang dipapar asap rokok - Meilina Tan (DiscoverSys Inc., 2017)
Aging is a physiological process that will be experienced by all living organism. In aging the accumulation of damage by free radicals in the cell all the time can cause cell damaging, disruption to cell death. Free radicals will attack cell membrane which is contain lipid bilayer (lipid peroxidation). In the state of oxidative stress, it required adequate and optimal antioxidant to the body. Smoking raises ROS which can cause oxidative stress through the mechanism of cell membrane lipid destruction. In this study use extra virgin olive oil (EVOO) contains phenolic, tocopherols, squalene, pigments and β- carotene which works to prevent oxidative stress from cigarette smoke. The aim of this study is to prove the effect of EVOO to decrease MDA level in male Wistar rats exposed by cigarette smokeThis experimental study has been conducted as pre-posttest control group design. 16 Wistar male rats used as a sample that was divided into 2 groups. Both group was exposed with cigarette smoke for 45 minute twice a day. Group 1 was the control group which were exposed to cigarette smoke and administered aquabides. Group 2 was the treatment group which were exposed to cigarette smoke and extra virgin olive oil oral dose 1cc (1gram/KgBW).Study result showed that MDA level pretest in control group was 9,3487 ± 0,69287 nmol/ml and treatment group was 8,8838 ± 0,63541 nmol/ml. Both group control and treatment of MDA level showed normal distribution and homogeneous. Comparability test for both group showed no significant differences MDA level between both group (p > 0,05). Result Posttest was, control group MDA level increased 10,2625 ± 0,53361 nmol/ml. This showed cigarette smoke in long term increased MDA level. Treatment group that was given extra virgin olive oil and cigarette smoke decreased MDA level into 3,4925 ± 0,85058 nmol/ml. This means statistically evaluated that the decrease of MDA in the treatment group was significantly different (p < 0,05). Paired T-test in control group pretest and posttest showed significant increased (p<0,05) and in treatment group pretest and posttest that was given extra virgin olive oil showed decreased of MDA level significantly (p<0,05). Independent T-test pretest between both group exposed by cigarette smoke showed no differences significantly (p>0,05) and for both group after given treatment EVOO showed significant differences (p<0,05).This study concluded that oral administration of extra virgin olive oil oral dose 1cc (1gram/KgBW) decreased MDA level in male Wistar rats exposed by cigarette smoke.